CONFLICTS OVER ILLEGAL, UNREPORTED AND UNREGULATED FISHING (IUU FISHING) IN THE SULAWESI SEAS - Muhamad, Nur Halima; Seniwati, Seniwati (Cahaya Ilmu Bangsa, 2024)
This article analyses the phenomenon of Illegal, Unreported and Unregulated (IUU) fishing in the seas of Sulawesi, a strategic region with abundant potential fisheries resources. The research uses a qualitative method with a literature review approach to explore the characteristics, economic and social impacts, and transboundary management efforts between Indonesia, Malaysia and the Philippines. The results showed that IUU fishing in Sulawesi waters is highly complex and involves various modus operandi, such as the use of foreign vessels with false flags, destructive fishing, and violation of fishing areas. The economic losses are significant, estimated at 30 trillion rupiah per year, resulting in depleted fish stocks, reduced income for local fishermen and threats to food security. Efforts are being made through multilateral approaches, such as the Trilateral Maritime Patrol, which integrates the maritime surveillance of the three countries. However, major challenges remain, including differences in law enforcement capabilities, overlapping regulations and potential collusion between IUU fishers and law enforcement officials.